Effect of Combined Exercises on Stair Negotiation Performance of Older Men: A Randomized Controlled Clinical Trial - Mehdi Ghaderian; Gholam Ali Ghasemi; Shahram Lenjannejadian; Ebrahim Sadeghi Demneh (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives The ability to safely walk up and down the stairs is an essential factor in older adults' independence and quality of life. This study aims to investigate the effect of combined exercises on stair negotiation performance of older men.  Methods & Materials In this randomized controlled clinical trial, 30 older men with at least 60 years of age living in Isfahan, Iran, in 2021 were selected who had functional independence, mental health, the ability to perform daily activities without using an assistive device, and without a history of falling. They assigned randomly to two parallel groups of intervention and control groups. Participants in the intervention group completed 12 weeks of combined exercise. The center of pressure (COP) parameters were measured by a force plate, and the time of stair ascending and descending was recorded by the Qualisys motion analysis system. The stair negotiation performance was evaluated by the timed up and down stairs (TUDS) test and the stair self-efficacy (SSE) scale. Data were analyzed by mixed ANOVA in SPSS software, version 24. The significance level was set at 0.05. Results The combined exercise program was effective in reducing the COP parameters during stairs ascending and descending (P<0.05). Stance time and time of ascending and descending decreased after the exercise (P≤0.034). The results of TUDS test (P≤0.002) and SSE scale (P≤0.048) showed improved performance in the intervention group compared to the control group. Conclusion The combined exercise program, by focusing on the factors such range of motion, strength, power, and balance, is effective in improving the stair negotiation performance of older men. Due to the prevalence of stair use in daily activities and its potential risk for older adults, this combined exercise program is recommended for older men.